Geometria del calcolo delle variazioni - Bompiani, E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
H. Busemann: The synthetic approach to Finsler spaces in the large.- E.T. Davies: Vedute generali sugli spazi variazionali.- D. Laugwitz: Geometrical methods in the differential geometry of Finsler spaces.- V.V. Wagner: Geometria del calcolo delle variazioni.
H. Busemann: The synthetic approach to Finsler spaces in the large -- E.T. Davies: Vedute generali sugli spazi variazionali -- D. Laugwitz: Geometrical methods in the differential geometry of Finsler spaces -- V.V. Wagner: Geometria del calcolo delle variazioni.
Keywords: Mathematics; Global differential geometry; Mathematical optimization; Mathematics; Differential Geometry; Calculus of Variations and Optimal Control; Optimization